ASSOCIATIONS OF AUDIOMETRIC HEARING, BRAIN MRI, AND COGNITIVE PERFORMANCE WITH SPEECH-IN-NOISE PERFORMANCE. (20th December 2022) - Jiang, Kening; Coresh, Josef; Hayden, Kathleen; Jack, Jr., Clifford; Mosley, Thomas; Pankow, James; Lin, Frank; Deal, Jennifer
Abstract: Speech-in-noise performance is fundamental to daily communications and comprehensive characterization is needed. We studied 590 dementia-free participants aged 70-84 years, including 428 hearing-impaired participants from the Aging and Cognitive Health Evaluation in Elders (ACHIEVE) study baseline (2018-19), which is a randomized controlled trial partially nested within the Atherosclerosis Risk in Communities (ARIC) Study, and 162 normal-hearing ARIC Visit 6/7 (2016-17/2018-19) participants. The Quick Speech-in-Noise (QuickSIN) test was used to measure speech-in-noise performance. Predictors included (1) Four-frequency better-ear pure-tone average (PTA); (2) Magnetic resonance imaging (MRI) measures (total and lobar volumes, diffusion tensor imaging, white matter hyperintensities); (3) Global and domain-specific (language, memory, executive function) cognitive performance. All predictors were standardized to Z-scores. We used multivariable-adjusted linear regression, adjusting for demographic and disease covariates. PTA and cognitive performance, but not MRI measures, were independently associated with speech-in-noise performance, with PTA explaining the largest variance, indicating the promising role of hearing aids.